Pengaruh Profitabilitas dan Likuiditas Terhadap Harga Saham Dengan Dividen Per Share Sebagai Variabel Moderating - Merida; Aprilia Sari, Petty (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To test the effect of profitability and liquidity on stock prices with dividends per share as a moderating variable in manufacturing companies listed on the IDX. Background Problems: As a result of the COVID-19 pandemic, the Indonesian capital market is currently under pressure and many issuers have experienced a decline in their share prices. Novelty: Testing the profitability and liquidity of the stock price moderated by the dividend per share. Research Methods: Using a purposive sampling method on 10 companies with predetermined criteria. Finding/Results: Profitability proxied by return on equity has a significant effect on stock prices, while liquidity has no effect, furthermore DPS is not able to moderate the ROE relationship on stock prices but is able to moderate the CR relationship. Conclusion: Profitability proxied by return on equity has a significant effect on stock prices, while liquidity has no effect, furthermore DPS is not able to moderate the ROE relationship on stock prices but is able to moderate the CR relationship.